Implementation of generalized mechanical interfaces - Spannraft, Lucie; Mergheim, Julia; Steinmann, Paul (Proceedings in Applied Mathematics and Mechanics, 2019)
For an accurate approximation of the mechanical behavior of interfaces undergoing tension, shear and in‐plane stretch deformation, the definition of an appropriate interface constitutive model is crucial. Distinct interface models, such as cohesive zone models are well investigated. However, only little research considering energetic interface models, especially inelastic models, and generalized mechanical interfaces is conducted. Although multiple possibilities to apply cohesive zone models in commercial software exist, to the authors' knowledge, the material properties provided are generally limited by basic cohesive laws and any definition of energetic interface models lacks. In order to benefit from the advantages of commercial FE software, a generalized mechanical interface model is implemented in ABAQUS. The employed constitutive model combines a cohesive zone model with an energetic interface model.<br